The Developing Of e-Consultations For Effectiveness of Mentoring Academy - Ahmad Cucus; Endang Kusnadi (International Conference on Engineering and Technology Development (ICETD), 2013)
e-Consultations is one of the technology trends that could not be separated from the internet, e-Consultations are an alternative media that can be used to the consultation, online consultation which would further be easier because not limited by time and place, but all of these activities can konultasi properly recorded and can be reused at any time. Seeing the advantages of e-Consultations so the authors try to apply it in the process of academic guidance contained withing the campus, as an important tool, sometimes many academic coaching problems, such as meeting duration and schedule of meetings between students and lecturers, with the implementation of e-Consultations expected to assist students and faculty in academic mentoring activities.